Jackfruit bronzing disease surveillance study in selected orchards of Peninsular Malaysia - Gan, H. Y.; Govender, N.; Wong, M. Y. (Faculty of Agricultural Sciences, Sabaragamuwa University of Sri Lanka, 2025)
Purpose: IIn Malaysia, jackfruit (variety Tekam Yellow) significantly contributes to the nation’s economy. The valuable fruit production is affected by jackfruit bronzing disease (JBD). Information on JBD occurrence in Peninsular Malaysia is necessary to develop effective disease control strategies. Hence, this study aimed to survey JBD occurrence and identify the corresponding causative pathogens in selected jackfruit orchards distributed in Peninsular Malaysia. Research Method: A total of eight jackfruit orchards from five states in Peninsular Malaysia were selected for JBD sampling. Fruit samples were described for characteristic symptoms and disease incidence was expressed in percentage. The causative pathogens were identified using morphological observation and molecular methods while the pathogenicity test was done using Koch’s Postulates. Findings: JBD incidence in Peninsular Malaysia ranged between 20.13-70.25%. JBD-causal pathogen isolation showed that the bacterium was gram-negative, oxidase-negative, and non-capsulated straight rod shape with an average size of 0.35 x 1.31 µm (facultative anaerobic). A DNA sequence analysis on the 16S rRNA gene indicated that 15 putative isolates were unique to P. stewartii and one to P. dispersal at a 99-100% similarity index. Pathogenicity test of the P. stewartii isolates showed JBD characteristic symptoms suggesting that JBD occurrence caused by P. stewartii is common in Peninsular Malaysia and the pathogen could co-exist with P. dispersa. Research Limitations: The number of orchards sampled in this study is low and therefore, the findings pose biases to a certain extent. Originality/Value: JBD occurrence is common in small jackfruit orchards in Peninsular Malaysia. JBD is primarily caused by P. stewartii while both P. stewartii and P. dispersa could co-exist in JBD pathosystem.